Properties of Ag/TiO2 and Ag/SiO2 nanoparticles and their effect on the photocatalytic properties of a semiconductor nanocomposite - Sharapov, I.; Omarova, G.; Sadykova, A.; Seliverstova, E. (Eurasian Physical Technical Journal, 2025)
The optical properties and the electric field distribution around silver nanoparticles coated with TiO2 or SiO2 shell have been studied. It is demonstrated that the presence of a shell around a plasmonic nanoparticle leads to a bathochromic shift in the maximum of its absorption band. The maximum electric field intensity around metal nanoparticles is radially concentrated, predominantly near the surface of the nanoparticles. The quantum efficiency, representing the ratio of emitted photons to absorbed photons, is nearly 50% higher for Ag/TiO2 nanoparticles compared to Ag/SiO2. In the presence of Ag/TiO2 and Ag/SiO2 core/shell nanoparticles the photocatalytic activity of the TiO2/rGO nanocomposite increases by 2.7 and 1.7 times, respectively. These changes are associated with improved charge transport properties of TiO2/rGO and possible hot electron injection from the nanoparticles into the semiconductor.
Keywords: plasmon; nanoparticles; optical properties; photocatalysis; nanocomposite